Paleoceanography and ice sheet variability offshore Wilkes Land, Antarctica-Part 3: Insights from Oligocene-Miocene TEX86-based sea surface temperature reconstructions - Hartman, Julian D.; Sangiorgi, Francesca; Salabarnada, Ariadna; Petersen, Francien; Houben, Alexander, J. P.; Schouten, Stefan; Brinkhuis, Henk; Escutia, Carlota; Bijl, Peter K. (Climate of the Past, 2018)
The volume of the Antarctic continental ice sheet(s) varied substantially during the Oligocene and Miocene ( ∼ 34-5Ma) from smaller to substantially larger than today, both on million-year and on orbital timescales. However, reproduction through physical modeling of a dynamic response of the ice sheets to climate forcing remains problematic, suggesting the existence of complex feedback mechanisms between the cryosphere, ocean, and atmosphere systems. There is therefore an urgent need to improve the models for better predictions of these systems, including resulting potential future sea level change. To assess the interactions between the cryosphere, ocean, and atmosphere, knowledge of ancient sea surface conditions close to the Antarctic margin is essential. Here, we present a new TEX86-based sea surface water paleotemperature record measured on Oligocene sediments from Integrated Ocean Drilling Program (IODP) Site U1356, offshore Wilkes Land, East Antarctica. The new data are presented along with previously published Miocene temperatures from the same site. Together the data cover the interval between 34 and 11Ma and encompasses two hiatuses. This record allows us to accurately reconstruct the magnitude of sea surface temperature (SST) variability and trends on both million-year and glacial-interglacial timescales. On average, TEX values indicate SSTs ranging between 10 and 21°C during the Oligocene and Miocene, which is on the upper end of the few existing reconstructions from other high-latitude Southern Ocean sites. SST maxima occur around 30.5, 25, and 17Ma. Our record suggests generally warm to temperate ocean offshore Wilkes Land. Based on lithological alternations detected in the sedimentary record, which are assigned to glacial-interglacial deposits, a SST variability of 1.5-3.1°C at glacial-interglacial timescales can be established. This variability is slightly larger than that of deep-sea temperatures recorded in Mg/Ca data. Our reconstructed Oligocene temperature variability has implications for ...